Sugarcane bagasse ash as replacement of cement mortar - Syazwana , Mohd Sukri (2013)
Mortar was consisted of Ordinary Portland Cement (OPC), fine aggregates and water. Blended cement contain pozzolanic reaction cement due to the present of pozzolanic materials like sugarcane bagasse ash (SCBA), fly ash ,palm oil fuel ash(POFA) and others. In this research the blended cement used was made up of SCBA. Bagasse is the fibrous residue of sugarcane after crushing and extraction of juice. In sugarcane bagasse it made up of water (about 50 percent), fiber (above 48 percent) and also some small amount of soluble solids. Mostly, bagasse produced is burnt for energy needed for sugar processing The use of sugarcane bagasse ash (SCBA) as cement replacement material to improves quality and reduce the cost of construction material such as mortar and concrete pa y ers. In this research, laboratory testing includes tests to determine the compressive strength of mortar containing sugarcane bagasse ash replace the Portland cement with different rates 0%, 5%, 10% and 15%. Portland cement will be used for all samples and mixtures. The project expected to get the result compressive strength by using sugarcane bagasse ash (SCBA) as replacement of cements in mortar. This testing is needed to know whether the strength can be acceptable or not when follow ASTM mix design standard. Secondly, this research was to know the porosity of mortar when replaced with different proportion of sugarcane bagasse ash with cement. The porosity test will help to know the porous of the samples when placed in differences condition.